2009
DOI: 10.1364/oe.17.006230
|View full text |Cite
|
Sign up to set email alerts
|

Whispering gallery mode carousel – a photonic mechanism for enhanced nanoparticle detection in biosensing

Abstract: Individual nanoparticles in aqueous solution are observed to be attracted to and orbit within the evanescent sensing ring of a Whispering Gallery Mode micro-sensor with only microwatts of driving power. This Carousel trap, caused by attractive optical gradient forces, interfacial interactions, and the circulating momentum flux, considerably enhances the rate of transport to the sensing region, thereby overcoming limitations posed by diffusion on such small area detectors. Resonance frequency fluctuations, caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
193
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(198 citation statements)
references
References 12 publications
3
193
1
1
Order By: Relevance
“…In addition, the average size of this gap should depend on P 0 , D, and on the concentration of ions in a suspension. It is likely that the average size of these gaps in our experiments was on the scale of few tenths of nanometers; 22,27 however, additional studies are required for more precise characterization of the gap sizes. This plays a critical role in achieving steady propelling along the fiber, because the spheres were covered with a sticky surfactant layer by the manufacturer and physical contact with the fiber would retard their motion.…”
Section: Giant Resonant Light Forces Yc LI Et Almentioning
confidence: 98%
See 3 more Smart Citations
“…In addition, the average size of this gap should depend on P 0 , D, and on the concentration of ions in a suspension. It is likely that the average size of these gaps in our experiments was on the scale of few tenths of nanometers; 22,27 however, additional studies are required for more precise characterization of the gap sizes. This plays a critical role in achieving steady propelling along the fiber, because the spheres were covered with a sticky surfactant layer by the manufacturer and physical contact with the fiber would retard their motion.…”
Section: Giant Resonant Light Forces Yc LI Et Almentioning
confidence: 98%
“…22 The origin of this gap has been studied in experiments on a WGM carousel, a photonic mechanism for trapping polystyrene nanoparticles in a circular motion around silica microspheres. 27 It has been demonstrated that the particle is radially trapped due to a combination of a long-range attractive interaction and a short-range repulsive interaction. The attractive optical force originates from the radial gradient of the evanescent fields.…”
Section: Giant Resonant Light Forces Yc LI Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…2b). We believe these events arise from the electrostatic repulsion between the microtoroid and nanorod surfaces, resulting in brief trapping of the nanorod followed by diffusion away from the resonator 14 .…”
mentioning
confidence: 99%